The Heritage of 30 Years of Mobile Communications in the UK. (2nd January 2016) - Linge, Nigel; Sutton, Andy
Abstract : The first mobile phone networks were launched in the UK in 1985. In the 30 years that have elapsed since then, the mobile phone has evolved from an expensive device owned by the few to a mass-market smartphone that is now regarded as an essential part of modern-day life. Behind the scenes, the mobile networks have undergone four major technology evolutions that have transformed their functionality from providing a basic telephone service to offering very high-speed connectivity for data applications. Yet, much of the heritage of this relatively young but transformational mobile technology is poorly documented and in great danger of being completely lost. Each new generation of mobile network replaces and ultimately erases the evidence of its predecessor. Equally, manufacturers are so focused on the release of their next handset that this leaves little scope or motivation for preserving and recording older models. The perception remains that the mobile phone is a new and young technology which is still considered by many to be a recent phenomenon. This results in a very casual attitude to the preservation of cellular mobile communications heritage, hence raising the significant risk that no suitable historical records will be available for future generations. This paper therefore begins to address this deficit by examining, through a UK perspective, two key but highly visible parts of the mobile phone story, namely, the cellular radio site installations that adorn roadsides, rooftops and hillsides and the mobile phones themselves as important historical artefacts.